Critical evaluation of climate syntheses to benchmark CMIP6/PMIP4 127 ka Last Interglacial simulations in the high-latitude regions. (15th July 2017) - Capron, E.; Govin, A.; Feng, R.; Otto-Bliesner, B.L.; Wolff, E.W.
Abstract: The Last Interglacial (LIG, ∼129-116 thousand years ago, ka) represents an excellent case study to investigate the response of sensitive components of the Earth System and mechanisms of high-latitude amplification to a climate warmer than present-day. The Paleoclimate Model Intercomparison Project (Phase 4, hereafter referred as PMIP4) and the Coupled Model Intercomparison Project (Phase 6, hereafter referred as CMIP6) are coordinating the design of (1) a LIG Tier 1 equilibrium simulation to simulate the climate response at 127 ka, a time interval associated with a strong orbital forcing and greenhouse gas concentrations close to preindustrial levels and (2) associated Tier 2 sensitivity experiments to examine the role of the ocean, vegetation and dust feedbacks in modulating the response to this orbital forcing. Evaluating the capability of the CMIP6/PMIP4 models to reproduce the 127 ka polar and sub-polar climate will require appropriate data-based benchmarks which are currently missing. Based on a recent data synthesis that offers the first spatio-temporal representation of high-latitude (i.e. poleward of 40°N and 40°S) surface temperature evolution during the LIG, we produce a new 126–128 ka time slab, hereafter named 127 ka time slice. This 127 ka time slice represents surface temperature anomalies relative to preindustrial and is associated with quantitative estimates of the uncertainties related to relative dating and surface temperature reconstruction methods. It illustrates warmer-than-preindustrial conditions in the high-latitude regions of both hemispheres. In particular, summer sea surface temperatures (SST) in the North Atlantic region were on average 1.1 °C (with a standard error of the mean of 0.7 °C) warmer relative to preindustrial and 1.8 °C (with a standard error of the mean of 0.8 °C) in the Southern Ocean. In Antarctica, average 127 ka annual surface air temperature was 2.2 °C (with a standard error of the mean of 1.4 °C) warmer compared to preindustrial. We provide a critical evaluation of the latest LIG surface climate compilations that are available for evaluating LIG climate model experiments. We discuss in particular our new 127 ka time-slice in the context of existing LIG surface temperature time-slices. We also compare the 127 ka time slice with the ones published for the 125 and 130 ka time intervals and we discuss the potential and limits of a data-based time slice at 127 ka in the context of the upcoming coordinated modeling exercise. Finally we provide guidance on the use of the available LIG climate compilations for future model-data comparison exercises in the framework of the upcoming CMIP6/PMIP4 127 ka experiments. We do not recommend the use of LIG peak warmth-centered syntheses. Instead we promote the use of the most recent syntheses that are based on coherent chronologies between paleoclimatic records and provide spatio-temporal reconstruction of the LIG climate. In particular, we recommend using our new 127 ka data-based time slice in model-data comparison studies with a focus on the high-latitude climate. Highlights: New 127 ka time slice based on a Last Interglacial high-latitude climate synthesis. Warmer-than-preindustrial 127 ka surface conditions in high-latitude regions. Benchmark to evaluate CMIP6/PMIP4 LIG simulations with 127 ka climate forcing. Critical evaluation of existing LIG climate compilations as a guidance for modelers.